BRAF mutations may identify a clinically distinct subset of glioblastoma - Samantha N. McNulty; Katherine E. Schwetye; Cole Ferguson; Chad E. Storer; George Ansstas; Albert H. Kim; David H. Gutmann; Joshua B. Rubin; Richard D. Head; Sonika Dahiya (Scientific Reports, 2021)
Abstract Glioblastoma (GBM) is the most common primary malignant brain tumor in adults. Prior studies examining the mutational landscape of GBM revealed recurrent alterations in genes that regulate the same growth control pathways. To this regard, ~ 40% of GBM harbor EGFR alterations, whereas BRAF variants are rare. Existing data suggests that gain-of-function mutations in these genes are mutually exclusive. This study was designed to explore the clinical, pathological, and molecular differences between EGFR- and BRAF-mutated GBM. We reviewed retrospective clinical data from 89 GBM patients referred for molecular testing between November 2012 and December 2015. Differences in tumor mutational profile, location, histology, and survival outcomes were compared in patients with EGFR- versus BRAF-mutated tumors, and microarray data from The Cancer Genome Atlas was used to assess differential gene expression between the groups. Individuals with BRAF-mutant tumors were typically younger and survived longer relative to those with EGFR-mutant tumors, even in the absence of targeted treatments. BRAF-mutant tumors lacked distinct histomorphology but exhibited unique localization in the brain, typically arising adjacent to the lateral ventricles. Compared to EGFR- and IDH1-mutant tumors, BRAF-mutant tumors showed increased expression of genes related to a trophoblast-like phenotype, specifically HLA-G and pregnancy specific glycoproteins, that have been implicated in invasion and immune evasion. Taken together, these observations suggest a distinct clinical presentation, brain location, and gene expression profile for BRAF-mutant tumors. Pending further study, this may prove useful in the stratification and management of GBM.